Is the time now ripe for South Africa to introduce a formal group tax system? - Joubert, Jacobus (Department of Finance and Tax, 2025)
The possible introduction of a group tax regime in South Africa has for some time been the subject of debate. In its third interim report the Katz commission recommended that South Africa employ a consolidation method of group taxation, this same method of group taxation was also proposed by the Davis Tax committee (“DTC”). Despite the proposal and other findings suggesting South Africa should adopt a group tax regime, the reality is that South Africa is yet to adopt this regime, but rather resorted to an interim regime, being the corporate rules currently employed. The dissertation addresses the crucial question of whether the time is now ripe for South Africa to adopt a formal group tax system, emphasizing the necessity for mutual benefit to both the fiscus and taxpayers. An examination of the existing corporate rules reveals their shortcomings and inability to deliver intended relief, prompting consideration of a group tax system as a viable alternative, indicating that the possibility of a group tax system should be investigated. A group tax system deems members of the same corporate group to be the same person for tax purposes. Group tax aligns with economic reality of groups whereby the companies within them are managed towards the greater good of the group and not the company itself. A system of group taxation strongly aligns with the single entity principle and achieves the objective policies of a good tax system. The Margo Commission, Katz Commission, and DTC, all support the finding that there are potentially significant benefits of a group tax system for South Africa. The major concern related to the introduction to group tax in South Africa remains SARS's ability to effectively implement and maintain it. It is submitted that SARS has made great strides in recent years and that the potential benefits of a group tax system should not be neglected. The conclusion is reached that the time is now ripe to introduce a group tax system to South Africa.